Application of a trait‐based climate change vulnerability assessment to determine management priorities at protected area scale. Issue 8 (6th July 2022) - Harper, Jack R. M.; van Wilgen, Nicola J.; Turner, Andrew A.; Tolley, Krystal A.; Maritz, Bryan; Clusella‐Trullas, Susana; da Silva, Jessica M.; Cunningham, Susan J.; Cheney, Chad; de Villiers, Atherton L.; Measey, John; Foden, Wendy
Abstract: Estimating and planning for the impacts of climate change on the biodiversity of protected areas is a major challenge for conservation managers. When these areas are topographically heterogenous and contain species' entire ranges, this challenge is exacerbated because the coarse spatial scales of Global Circulation Model projections provide limited information for within‐park management. South Africa's Table Mountain National Park, home to three endemic amphibian species in just 24, 500 hectares, provides a case study for identifying conservation needs under climate change. Selecting the park's herpetofauna as pilot taxa, we identified life history and demographic characteristics believed to make species more sensitive and less able to adapt to climate change. We organized these into assessment frameworks and, through a combination of literature review and expert elicitation, reviewed and used them to assess climate change vulnerability of 18 amphibian and 41 reptile species. The assessment highlighted that 73% and 67% of the park's reptile and amphibian species, respectively, had at least one high‐sensitivity and low‐adaptive capacity trait. Using ordinal and additive scoring methods, we identified the species most vulnerable to climate change and highlight the park areas containing their highest concentrations. These areas will be used to inform landscape‐scale management priorities and park use zones. The current IUCN Red List assessments for these species do not incorporate climate change vulnerability. Considering some species appear to be threatened by climate change, their conservation needs might be underestimated. Identifying the most vulnerable species and the mechanisms underpinning their vulnerability can guide the identification and prioritization of conservation needs, while the highlighted knowledge gaps inform priorities for monitoring and research. While comprehensive climate change adaptation planning for Table Mountain National Park requires additional assessment of other taxonomic groups, this trait‐based assessment example highlights a viable tool for assessing climate change vulnerability in protected areas. Abstract : We describe a trait‐based climate change vulnerability assessment of the herpetofauna of Table Mountain National Park. We highlight how the method can be used by conservation planners and practitioners to identify priority species and adaptive management requirements at the scale of a single protected area.